Changes of Morphology, Chemical Compositions, and the Biosynthesis Regulations of Cuticle in Response to Chilling Injury of Banana Fruit During Storage - Huang, Hua; Wang, Ling; Qiu, Diyang; Zhang, Nan; Bi, Fangcheng (Frontiers in Plant Science, 2021)
The plant cuticle covers almost all the outermost surface of aerial plant organs, which play a primary function in limiting water loss and responding to the environmental interactions. Banana fruit is susceptible to thermal changes with chilling injury below 13°C and green ripening over 25°C. Herein, the changes of surface morphology, chemical compositions of cuticle, and the relative expression of cuticle biosynthesis genes in banana fruit under low-temperature storage were investigated. Banana fruit exhibited chilling injury rapidly with browned peel appearance stored at 4°C for 6 days. The surface altered apparently from the clear plateau with micro-crystals to smooth appearance. As compared to normal ones, the overall coverage of the main cuticle pattern of waxes and cutin monomers increased about 22% and 35%, respectively, in browned banana stored under low temperature at 6 days. Fatty acids (C16–C18) and ω-OH, mid-chain-epoxy fatty acids (C18) dominated cutin monomers. The monomers of fatty acids, the low abundant ω, mid-chain-diOH fatty acids, and 2-hydroxy fatty acids increased remarkably under low temperature. The cuticular waxes were dominated by fatty acids (> C19), n-alkanes, and triterpenoids; and the fatty acids and aldehydes were shifted to increase accompanied by the chilling injury. Furthermore, RNA-seq highlighted 111 cuticle-related genes involved in fatty acid elongation, biosynthesis of very-long-chain (VLC) aliphatics, triterpenoids, and cutin monomers, and lipid-transfer proteins were significantly differentially regulated by low temperature in banana. Results obtained indicate that the cuticle covering on the fruit surface was also involved to respond to the chilling injury of banana fruit after harvest. These findings provide useful insights to link the cuticle on the basis of morphology, chemical composition changes, and their biosynthesis regulations in response to the thermal stress of fruit during storage.